Crop diversification and tropical herbivores : effects of intercropping and mixed varieties on the cassava whiteflies, aleurotrachelus socialis bondar and trialeurodes variabilis (quaintance), in Colombia / [mikrofilem] - 432639 Gold, Clifford Scott
Thesis (PhD) - University of California, Berkeley, 1987